2022
DOI: 10.1007/s12672-022-00557-3
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 dual regulation of the stability of LINC00662 and VEGFA RNAs promotes colorectal cancer angiogenesis

Abstract: Purpose The angiogenesis is among the primary factors that affect tumor recurrence and distant organ metastasis in colorectal cancer (CRC). N 6-methyladenosine (m6A) modification is one of the most common chemical modifications in eukaryotic mRNA, especially at the post-transcriptional level. Methyltransferase-like 3 (METTL3) promoting angiogenesis in a variety of tumors has been reported. However, the mechanism of how METTL3 dual-regulates the stability of long non-codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…RNA sequencing suggested SNHG10 upregulated expression in EMT‐derived exosomes 39,40 . Zhang et al found that METTL3 maintained VEGFA RNA stability to promote angiogenesis in CRC in vitro 41 . Methyltransferase‐like 3 upregulated PLAU mRNA through m6A modification, and regulated the MAPK/ERK pathway to promote angiogenesis and invasion in CRC 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA sequencing suggested SNHG10 upregulated expression in EMT‐derived exosomes 39,40 . Zhang et al found that METTL3 maintained VEGFA RNA stability to promote angiogenesis in CRC in vitro 41 . Methyltransferase‐like 3 upregulated PLAU mRNA through m6A modification, and regulated the MAPK/ERK pathway to promote angiogenesis and invasion in CRC 42 .…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 Zhang et al found that METTL3 maintained VEGFA RNA stability to promote angiogenesis in CRC in vitro. 41 Methyltransferase‐like 3 upregulated PLAU mRNA through m6A modification, and regulated the MAPK/ERK pathway to promote angiogenesis and invasion in CRC. 42 Overexpression of METTL3 led to upregulation of proliferative CRC cells to promote further migration.…”
Section: Discussionmentioning
confidence: 99%
“…VEGFA is an essential member of vascular endothelial growth factor family and a crucial regulator of vasculogenesis and angiogenesis, with multiple signaling pathways and factors involved in the regulation of its expression. M6A modification facilitated the stability of VEGFA by preventing its mRNA degradation in colorectal cancer ( Zhang G. et al, 2022 ; Liu X. et al, 2022 ). Moreover, in bone mesenchymal stem cells, m6A modification participated in regulating the alternative splicing of VEGFA ( Tian et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, METTL3 enhances m6A modification of VEGF-A which improves it interaction with IGF2BP2/3 and impedes the degradation of VEGF-A mRNA (Liu et al 2022a , b ; Yang et al 2020 ). The study of Zhang G et al also showed that METTL3 could enhance VEGF-A mRNA stability and protein level in colorectal cancer (Zhang et al 2022 ). In addition, m6A methylation of the internal ribosome entry site sequence A (IRES-A) at VEGF-A 5'UTR recruits the YTHDC2/eIF4GI complex to facilitate its’ cap-independent translation initiation (Zhang et al 2023 ).…”
Section: Regulation Of Vegf-a Expression In Tumorsmentioning
confidence: 99%